2019
DOI: 10.1002/jcph.1448
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Magnesium Sulfate Dosing Regimens for Women With Preeclampsia: A Population Pharmacokinetic Exposure‐Response Modeling and Simulation Study

Abstract: Magnesium sulfate is the anticonvulsant of choice for eclampsia prophylaxis and treatment; however, the recommended dosing regimens are costly and cumbersome and can be administered only by skilled health professionals. The objectives of this study were to develop a robust exposure‐response model for the relationship between serum magnesium exposure and eclampsia using data from large studies of women with preeclampsia who received magnesium sulfate, and to predict eclampsia probabilities for standard and alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Further prospective cohort studies with a larger sample size are necessary to draw any definitive conclusions on these issues. 5The minimum effective treatment concentration of MgSO 4 for prophylaxis and treatment of severe PE has largely been based on clinical and laboratory observations in earlier studies rather than standard exposure-response studies [6,12] .Although some pharmacokinetic studies of MgSO 4 administration in preeclamptic women are reported [29][30][31][32], there has been no rigorous evaluation of therapeutic serum magnesium concentration [11]. In the future, we will conduct a prospective study on whether patients with severe PE can achieve effective treatment concentration with MgSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Further prospective cohort studies with a larger sample size are necessary to draw any definitive conclusions on these issues. 5The minimum effective treatment concentration of MgSO 4 for prophylaxis and treatment of severe PE has largely been based on clinical and laboratory observations in earlier studies rather than standard exposure-response studies [6,12] .Although some pharmacokinetic studies of MgSO 4 administration in preeclamptic women are reported [29][30][31][32], there has been no rigorous evaluation of therapeutic serum magnesium concentration [11]. In the future, we will conduct a prospective study on whether patients with severe PE can achieve effective treatment concentration with MgSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the maternal demographic characteristics, lab test results, the regimens for the administration of MgSO 4 , and serum magnesium levels of the patients in the two groups. The Standard group and Sub-standard group showed no signi cant difference in age (28.00 vs. 31 .007), and higher measurement time (5.00 vs. 1.00, P=0.013) than women in Sub-standard group (P < 0.05). Through univariate analysis, we found that weight, BMI, Ccr, albumin, measurement time, and whether the loading dose was given were statistically signi cant risk factors for sub-therapeutic blood magnesium concentration (P < 0.1, Table 2).…”
Section: Resultsmentioning
confidence: 80%
“…Further prospective cohort studies with a larger sample size are necessary to draw any de nitive conclusions on these issues. (5) The minimum effective treatment concentration of MgSO 4 for prophylaxis and treatment of severe PE has largely been based on clinical and laboratory observations in earlier studies rather than standard exposure-response studies [6,12] .Although some pharmacokinetic studies of MgSO 4 administration in preeclamptic women are reported [29][30][31][32] , there has been no rigorous evaluation of therapeutic serum magnesium concentration [11] . In the future, we will conduct a prospective study on whether patients with severe PE can achieve effective treatment concentration with MgSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Further prospective cohort studies with a larger sample size are necessary to draw any de nitive conclusions on these issues. (5) The minimum effective treatment concentration of MgSO 4 for prophylaxis and treatment of severe PE has largely been based on clinical and laboratory observations in earlier studies rather than standard exposure-response studies [6,17] Although some pharmacokinetic studies of MgSO 4 administration in preeclamptic women are reported [25][26][27][28][29] , there has been no rigorous evaluation of therapeutic serum magnesium concentration [14] .…”
Section: Discussionmentioning
confidence: 99%